Analisis Numerik Pengaruh Variasi Tinggi Vortex Generator terhadap Karakteristik Aerodinamika Sayap Berbasis Computational Fluid Dynamics (CFD) - Perkasa, Rilis Eka; Mashudi, Imam; Gunawan, Chandra; Amrullah, Utsman Syah (Jurnal Teknik Terapan, 2025)
A vortex generator is an aerodynamic device installed on wings or other surfaces to enhance lift and delay stall at high angles of attack. This study aims to analyze the effect of vortex generator installation on the aerodynamic characteristics of a straight wing. Numerical simulations were conducted using the computational fluid dynamics (CFD) method on a three-dimensional wing model with a NACA 4412 airfoil section. Triangular vortex generators with heights of 10 mm and 20 mm were applied, while a clean wing without vortex generator was used as a reference. The wing was subjected to an airflow velocity of 50 m/s at several angles of attack. The main parameters observed were the lift coefficient (CL), drag coefficient (CD), and flow visualization around the wing surface. The simulation results show that the addition of a 10 mm vortex generator increases CL at higher angles of attack compared to the clean wing. In contrast, the installation of a 20 mm vortex generator primarily resulted in a higher CD and did not provide a positive contribution to lift performance. Overall, it could be concluded that  for this research configuration, the 10 mm vortex generator increase the aerodynamic performance of the wing.